Species-specific responses of young deciduous and coniferous trees to simulated particulate matter - Varnagirytė-Kabašinskienė, Iveta; Černiauskas, Valentinas (Frontiers in Plant Science, 2025)
IntroductionParticulate matter (PM) is a significant air pollutant associated with severe health and environmental issues. Although urban trees help filter PM through their leaves and surfaces, PM pollution disrupts their structure and function at various levels, affecting photosynthesis, blocking stomata, and inducing oxidative damage.MethodsThis study evaluated the growth, biomass, and physiological responses of five tree species - silver birch (Betula pendula), small-leaved lime (Tilia cordata), Norway maple (Acer platanoides), Scots pine (Pinus sylvestris), and Norway spruce (Picea abies) - to artificial PM exposure. One- to two-year-old seedlings were divided into control and PM-treated groups.Results and DiscussionNorway maple and small-leaved lime were the most resilient, maintaining growth and activating stress defences. Silver birch showed moderate tolerance, with biochemical compensation despite growth suppression. Norway spruce experienced a moderate decline in physiological balance and growth. Scots pine was the most sensitive, displaying reduced growth and heightened oxidative stress. The study highlighted the importance of species selection for urban planting. Due to their PM tolerance, Norway maple and small-leaved lime appear to be best suited for polluted environments. Silver birch and Norway spruce may be suitable for moderately polluted areas, while Scots pine is less ideal for high-pollution urban settings. These findings support the concept of environmental hormesis, where low-dose stressors elicit adaptive responses in tolerant species. However, the observed species-specific responses and the broader applicability of the results may be constrained by several factors, including the use of relatively young seedlings, the limited duration of exposure, and the specific method of simulating PM pollution.